Impact of BIM-related factors affecting construction project performance - Nguyen Van Tam; Nguyen, Quoc Toan; Vu Van Phong; Durdyev, Serdar (Structural survey, 2023)
PurposeThis study aims to investigate the impact of primary building information modelling (BIM)-related factors, extracted from the literature on the subject, on construction project performance.Design/methodology/approachBased on data collected from 134 BIM users, this study used structural equation modelling to assess the impact of these factors in five main BIM-related factor clusters.FindingsThe results of the analysis confirmed the reliability and validity of the research design and outcomes. The findings indicated that the BIM-related external factors cluster is the most influential cluster affecting construction project performance. BIM-related project factors and BIM-related technological factors also had a significant impact on project performance. These were followed by the BIM-related management factors cluster, while the BIM-related human factors cluster had a low impact on project performance.Research limitations/implicationsThis study will contribute to fostering BIM adoption and implementation in the construction industry in developing countries.Originality/valueThis study has filled a crucial knowledge gap by providing information on manageable primary BIM-related factors affecting construction project performance.